2016
DOI: 10.1142/s2010324716500016
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel Magnetoresistance and Temperature Related Effects in Magnetic Tunnel Junctions with Embedded Nanoparticles

Abstract: Temperature dependence of the tunnel magnetoresistance (TMR) was calculated in range of the quantum-ballistic model in the magnetic tunnel junction (MTJ) with embedded nanoparticles (NPs). The electron tunnel transport through NP was simulated in range of double barrier approach, which was integrated into the model of the magnetic point-like contact. The resonant TMR conditions and temperature impact were explored in detail. Moreover, the possible reasons of the temperature induced resonant conditions were dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In our previous works 17 19 we showed that regime of the quantized conductance due to direct double barrier tunneling ( a = 1) is a main reason of anomalous TMR behaviors, confirming the lack of CB effects for the small NPs, d < 3.5 nm, in these systems. Our basic tunneling approach has similar origin with the theory of giant magnetoresistance in point-like contacts 20 reproducing the limit of the point-like contact when NP touches top and bottom FMLs.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our previous works 17 19 we showed that regime of the quantized conductance due to direct double barrier tunneling ( a = 1) is a main reason of anomalous TMR behaviors, confirming the lack of CB effects for the small NPs, d < 3.5 nm, in these systems. Our basic tunneling approach has similar origin with the theory of giant magnetoresistance in point-like contacts 20 reproducing the limit of the point-like contact when NP touches top and bottom FMLs.…”
Section: Introductionsupporting
confidence: 75%
“…The fraction is defined as a set of TCs with the same size of NPs. The ballistic tunneling was considered as a basic transport approach, and the current for each TC was defined as follows 18 , 19 :
Figure 1 Schematic model of the NP-MTJ. Blue and red arrows show parallel (P) and anti-parallel (AP) magnetic configurations, respectively.
…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have studied the effects associated with the geometric parameters of the domain wall and its dynamics [9][10][11] , the geometry and electronic structure of the contacts 12 , as well as the type of the contact separating area 13,14 . In recent works 15,16 , the behavior of TMR in tunnel junctions with embedded nanoparticles was investigated. The maximum value of TMR in such structures was found to lies close to 300 %.…”
Section: Introductionmentioning
confidence: 99%